The effects of resistance training experience on movement characteristics in the bench press exercise - Maszczyk, A.; Wilk, M.; Krzysztofik, M.; Gepfert, M.; Zajac, A.; Petr, M.; Stastny, P. (Biology of Sport, 2020)
The main aim of this study was to determine whether the level of experience in strength training has a significant effect on differences in the value of exercise volume determined on time under tension (TUT) and number of repetition (REP) for a specific movement tempo. The study examined 68 men divided into groups of beginners and advanced strength trained athletes. The participants performed 5 sets of bench press (BP) at 70% 1RM using either a REG, MED or SLOW metronome guided cadence. Each set was performed to failure and with 3 min of rest between sets. Significant differences in TUT were found between the groups of beginners and advanced athletes for the slow (SLO) 6/0/4/0 tempo in set 1 (p = 0.01) and set 2 (p = 0.04), and for the regular (REG) 2/0/2/0 tempo in set 5 (p = 0.01). Significant differences were documented for total TUT between the beginners and advanced athletes for the SLO 6/0/4/0 tempo (p = 0.04). The results of ANOVA revealed significant differences in the number of repetitions between groups for the SLO 6/0/4/0 tempo in set 4 (p = 0.04) and set 5 (p = 0.04), and for the REG 2/0/2/0 tempo in set 5 (p = 0.01). The main finding of this study is that strength training experience has a significant effect on training volume, both in terms of TUT and REP at a specific constant movement tempo. Significant differences do not occur for each value of the tempo used.